The Role of Classical Literary Theory in Identity Formation: Insights from Plato, Aristotle, and Horace - Anireddy, Abhiram Reddy (Journal of Research in Vocational Education, 2026)
This research explores the role of literature in shaping personal identity, as examined through the lens of classical philosophers Plato, Aristotle, and Horace. The study critically analyzes their respective views on how literature influences morality, emotion, and rationality, providing insight into their varying perspectives on the relationship between literature and identity formation. The paper compares their philosophies, highlighting the enduring significance of these ancient theories in contemporary discussions of literature and self-identity. The study is significant as it bridges classical and contemporary discussions on the influence of literature on identity formation, offering a historical perspective that enhances our understanding of the cultural and psychological impact of literary works.